Planning Bibliography Series No. 95 Centre State Relations Vis-a-vis Planning in India (No. 4) - Planning Commission (Planning Commission Government of India, 1971)
This bibliographic compilation from the Planning Commission Library provides a comprehensive overview of Centre-State relations in India, particularly in the context of planning and policy implementation. The document curates books, articles, editorials, and notes, categorizing them into key themes such as governance frameworks, fiscal autonomy, economic development, and regional disparities. It highlights how Centre-State dynamics influence resource allocation, state autonomy, and the effectiveness of national development plans. By including state-specific studies and analyzing constitutional and financial arrangements, the bibliography serves as an essential resource for researchers and policymakers, offering insights to optimize intergovernmental relations and promote equitable growth across India.
Planning Commission Library New Delhi April 6, 1977/Chaitra 16, 1899
Keywords: Centre-State Relations; Planning; India; Governance; Fiscal Autonomy; Economic Development; Policy Implementation; Resource Allocation; Constitutional Framework; Regional Disparities; State Autonomy; Bibliography